Domestication and evolutionary histories of specialized gut symbionts across cephalotine ants - Christian Cabuslay; John T. Wertz; Benoît Béchade; Yi Hu; Sonali Braganza; Daniel Freeman; Shreyansh Pradhan; Maria Mukhanova; Scott Powell; Corrie Moreau; Jacob A. Russell (Molecular Ecology, 2024)
The evolution of animals and their gut symbionts is a complex phenomenon, obscured by lability and diversity. In social organisms, transmission of symbionts among relatives may yield systems with more stable associations. Here, we study the history of a social insect symbiosis involving cephalotine ants and their extracellular gut bacteria, which come predominantly from host‐specialized lineages. We perform multi‐locus phylogenetics for symbionts from nine bacterial orders, and map prior amplicon sequence data to lineage‐assigned symbiont genomes, studying distributions of rigorously defined symbionts across 20 host species. Based on monophyly and additional hypothesis testing, we estimate that these specialized gut bacteria belong to 18 distinct lineages, of which 15 have been successfully isolated and cultured. Several symbiont lineages showed evidence for domestication events that occurred later in cephalotine evolutionary history, and only one lineage was ubiquitously detected in all 20 host species and 48 colonies sampled with amplicon 16S rRNA sequencing. We found evidence for phylogenetically constrained distributions in four symbionts, suggesting historical or genetic impacts on community composition. Two lineages showed evidence for frequent intra‐lineage co‐infections, highlighting the potential for niche divergence after initial domestication. Nearly all symbionts showed evidence for occasional host switching, but four may, more often, co‐diversify with their hosts. Through our further assessment of symbiont localization and genomic functional profiles, we demonstrate distinct niches for symbionts with shared evolutionary histories, prompting further questions on the forces underlying the evolution of hosts and their gut microbiomes.